Hadith on Avoiding Boredom in Learning from The Perspective of Educational Psychology - Dwi Yanti, Nurul Azizah; Hartati, Hartati; Muthi'ah, Anisatun (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2023)
Hadith is the second source of Islamic knowledge after the Quran. This means that hadith covers all aspects of activities that can be used as a reference, including education and the sciences that it encompasses. The problem in the world of education today is that teachers and students are forced to use a limited range of learning methods. This condition is caused by the lack of activities and creativity that educators and students engage in during the learning process. This situation has occurred during the time of the Prophet Muhammad, and hadiths related to avoiding boredom in learning have emerged. From this issue, research objectives were established. The purpose of this research is to determine the quality, quantity, and meaning of hadiths related to avoiding boredom in learning from the perspective of educational psychology that is adjusted to teaching strategies. The method used in this study is literature review (pentakhrijan hadith). The results of the study indicate that (1) the hadith "avoiding boredom in learning" is narrated by four mukharij (Bukhari, Muslim, Tirmidhi, and Ahmad) with thirteen sanad that are ṡiqah, connected by the year of death, place of residence, and teacher and student. Thus, this hadith can be categorized as a ṣahih li żātihi hadith. The quantity of this hadith is included as a Hadith Ahad with a garib category, (2) the meaning of this hadith can be related to educational psychology, because the habit of the Prophet in choosing the right day to provide appropriate education based on educational psychology.